Food Colors as the Factor of Development of Nephropathy in Children - V.A. Golovachova (Zaslavsky O.Yu., 2016)
The increase in the incidence of nephropathy arouses concern and necessitates the further study of kidney disease factors in the children. Objective: to determine the effect of food colors on the development of kidney pathology in the children. Materials and methods. We observed 199 children aged from 1 year to 17 years, who were divided into two groups: group 1 - 103 children with various renal diseases, group 2 - 96 somatically healthy children. Effect of food colors on children's kidneys was studied using a questionnaire survey of parents and the child. Results. Mothers of children with kidney disease significantly more frequently had used foods containing food colors (ice cream, confectionery, candies, soft drinks, such as fanta, lemonade, etc.) before, during and after pregnancy. The same situation is observed when determining the frequency of using food colors by children: children from group 1 in 14.5 % of cases eat such products continuously, in 36.9 % of cases - often, but not every day, and in 29.1 % of cases - several times a month. While children from group 2 constantly consume foods with food colors only in 4.2 % of cases, often, but not every day - in 20.8 % of cases, several times a month - in 29.1 %. Conclusion. Various environmental factors, such as food colors, influence the development of the child's body, reducing the adaptive capacity of the kidneys, or directly affecting them.